Boss witch - Aguirre, Ann (Aguirre, Ann. Fix-it witches, 2022)
"Clementine Waterhouse is a perfectly logical witch. She doesn't tumble headlong into love. Rather she weighs the pros and cons and decides if a relationship is worth pursuing. At least that's always been her modus operandi before. Clem prefers being the one in charge, always the first to walk away when the time is right. Attraction has never struck her like lightning. Until the witch hunter comes to town. Gavin Rhys hates being a witch hunter, but his family honor is on the line, and he needs to prove he's nothing like his grandfather, a traitor who let everyone down. But things in St. Claire aren't what they seem, and Gavin is distracted from the job immediately by a bewitching dark-haired beauty with a sexy smile and haunting secrets in her eyes. With so much at stake for them both, the last thing either can afford to lose is their hearts"--